Impacted Lower Third Molar Profile at Dental Hospital of Padjadjaran University - Muhammad Fauzi Akbar; Indra Hadikrishna; Lucky Riawan; Yurika Ambar Lita (Indonesian Dental Association, 2022)
Introduction: Impacted teeth are teeth that erupt incompletely in the normal eruption period. This situation can be caused by hard or soft tissue obstructions or a lack of arch jaw. Objectives: This study aimed to determine the impacted lower third molar teeth profile by age, sex, class, angulation, treatment, and anesthesia at RSGM UNPAD in 2017-2019. Methods: The study was conducted from February 8, 2020, to March 8, 2020. The study represents the impacted lower third molar teeth profile of patients referred to Outpatient Installation, Central Surgical Installation, and the Radiology Installation. Classification of tooth impaction was based on Pell & Gregory and Winter classifications using ImageJ application, while Intraclass Correlation Coefficient (ICC) was used to confirm data validity. Results: There were 146 impacted dental cases, with a total case of 62 (42.5%) for males and 84 (57.5%) for females. Most impacted teeth occurred in the 12-25 years age group up to 72 (49.3%). A total of 177 impacted teeth mostly occurred in 48 teeth, as many as 91 (51.4%). Impaction class Pell & Gregory class B with 110 (62.1%) cases were found the most. Based on the anterior border of ramus, class II with 164 (91.1%) cases was found the most. Horizontal (79 cases, 44.6%) became the most frequent angulation. The procedures taken were all odontectomy 177 (100%) with more use of local anesthesia 136 (93.2%) compared to general anesthesia 10 (6.8%). Conclusion: Cases of impacted lower third molar teeth at RSGM UNPAD in 2017-2019, were most common in females and mostly in the 12-25 years age group, with Pell & Gregory class IIB classification and Winter horizontal angulation classification, all procedures performed were odontectomy, majority using local anesthesia.